Comparison of Transbuccal versus Transoral Approaches for Management of Mandibular Angle Fractures - Ali Abu Bakar, Sadiq Ali, Muhammad Nauman, Khaqan Azam, Muhammad Akram, Fareed-ud-Din Ahmad Chishti, Navaira Tariq, Urooj Kirmani, Aqsa Fatima (Pakistan Journal of Medical & Health Sciences, 2025)
Background: The majority of mandibular fractures are angle fractures. A third molar, a smaller cross-sectional area, muscular tensions at the angle region, and a sudden change from horizontal to vertical rami form cause this event. Objective: To compare the outcome of transbuccal versus transoral approach for managementof mandibular angle fractures. Study design: Quasi experimental Place and duration of study: Department of Oral & Maxillofacial Surgery, Lahore Medical & Dental College, Lahore from 15th April 2020 to 15th October 2020. Methodology: Ninety participants were enrolled and divided in two groups; transbuccal approach and transoral approach. Each group comprised 45 patients. An incision was made within the mouth using the transbuccal technique, beginning at the level of the maxillary occlusal plane and moving forward along the front border of the ascending ramus of the mandible. Additionally, the trocar was inserted across the mandibular angle area via a minor incision that was created outside the mouth, measuring 2-3mm. A 2.5 mm miniplate with four holes was used to straighten and stabilize the fracture. An incision was made only within the mouth using the transoral technique, beginning at the level of the maxillary occlusal plane, on the front edge of the ascending ramus of the mandible. A 2.5 mm 4-hole mini-plate was used to immobilize and secure the fracture segments. Results: There were 31 (68.8%) males and 14 (31.2%) females in transbuccal approach while in transoral technique, 29 (64.4%) males and 16 (35.6%) females. Twenty two (48.9%) transbuccal and 19 (42.2%) transoral left mandibular angle fracture patients. Patients with excellent surgical access were 31 (68.8%) transbuccal and 19 (42.2%) transoral. Transbuccal averaged 83.89 minutes and transoral 81.51. Six (13.3%) transbuccal and 7 (15.5%) transoral individuals had similar occlusion. No group had significant difference in occlusion. Conclusion: The trans-buccal method is advantageous for surgical access (P<0.05 vs. trans-oral approach).Mean transoral surgical time was less than transbuccal, but not statistically significant. Keywords: Mandibular angle fracture, Transoral approach, Transbuccal approach, Single miniplate.